Analisis Kinerja Anggaran Pendapatan Dan Belanja Daerah Dalam Laporan Realisasi Anggaran Untuk Menilai Kinerja Keuangan Pada Badan Keuangan Dan Aset Daerah Kota Medan Tahun Anggaran 2018-2023 - Tasya Rahmadani; Ruswan Nurmadi; Muhammad Arief (Jurnal Manajemen Dan Akuntansi Medan, 2025)
The purpose of this research was to assess the financial performance of the Medan City Government by analyzing budget performance for the 2018-2023 fiscal year. The object of this research is the Regional Finance and Asset Agency of Medan City. The analysis method used is descriptive quantitative which is done by making a description of the problems that have been identified. The results of this research indicate that the analysis of revenue variance has a negative difference, revenue growth experiences fluctuating growth with the degree of decentralization is considered good, the effectiveness ratio of Regional Original Revenue shows less effective. The expenditure variance analysis can be categorized as good, the compatibility of operating expenditure is considered very harmonious, the compatibility of capital expenditure is considered not harmonious, and the effectiveness ratio of regional expenditure is said to be efficient. So it can be said that the condition of the financial capacity of Medan City is still not ideal with fluctuating growth and less effective. In addition, the performance of expenditure can be said that the Medan City Government is considered less harmonious and has made efficiency in the use of the budget.